2021
DOI: 10.1038/s41598-020-79466-w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action and potential applications of selective inhibition of microsomal prostaglandin E synthase-1-mediated PGE2 biosynthesis by sonlicromanol’s metabolite KH176m

Abstract: Increased prostaglandin E2 (PGE2) levels were detected in mitochondrial disease patient cells harboring nuclear gene mutations in structural subunits of complex I, using a metabolomics screening approach. The increased levels of this principal inflammation mediator normalized following exposure of KH176m, an active redox-modulator metabolite of sonlicromanol (KH176). We next demonstrated that KH176m selectively inhibited lipopolysaccharide (LPS) or interleukin-1β (IL-1β)-induced PGE2 production in control skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
1
12
0
1
Order By: Relevance
“…7H-4MC reduces the release of inflammatory mediators and pro-inflammatory cytokines PGE 2 , an important inflammatory mediator, is produced from arachidonic acid by COX-2. In a variety of inflammatory cells, including macrophages, COX-2 expression is induced by cytokines and other activators, such as LPS, which results in the release of a large amount of PGE 2 at inflammatory sites [18][19]. We examined the effects of 7H-4MC on PGE 2 production, which was quantified in the supernatants of LPS-induced RAW 264.7 macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7H-4MC reduces the release of inflammatory mediators and pro-inflammatory cytokines PGE 2 , an important inflammatory mediator, is produced from arachidonic acid by COX-2. In a variety of inflammatory cells, including macrophages, COX-2 expression is induced by cytokines and other activators, such as LPS, which results in the release of a large amount of PGE 2 at inflammatory sites [18][19]. We examined the effects of 7H-4MC on PGE 2 production, which was quantified in the supernatants of LPS-induced RAW 264.7 macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…7H-4MC suppresses LPS-induced degradation of IκB-α protein In the NF-κB signaling pathway, NF-κB binds to its inhibitor protein, IκB-α, and resides in the cytoplasm of unstimulated cells. Its activation is regulated by the degradation of IκB-α, which frees NF-κB and allows its translocation to the nucleus [18][19][20]. To better demonstrate the mechanisms involved in the inhibitory effect of 7H-4MC on the LPS-induced release of inflammatory mediators, the protein levels of IκB-α were examined by western blotting.…”
Section: H-4mc Inhibits Lps-induced Inos and Cox-2 Protein Expressionmentioning
confidence: 99%
“…Based on our previous work in fibroblasts and macrophage-like RAW264.7 cells, addition of exogenous PGE 2 reversed the effect of KH176m on mPGES-1 expression, suggesting a PGE 2 -driven positive feedback control of mPGES-1 transcriptional regulation, which was directly inhibited by KH176m [35]. We therefore hypothesized that also in the PCa cells inhibition of mPGES-1 expression and spheroid growth by KH176m will be restored by administration of exogenous PGE 2 .…”
Section: Effect Of Kh176m On Spheroid Growth and Expression Of Mpges-1 Is Overcome By Exogenous Addition Of Pge2mentioning
confidence: 85%
“…Indeed, we found that the mPGES-1 protein and mRNA expression were significantly decreased by KH176m in DU145 derived spheroids while other key genes involved in PGE 2 synthesis remained unchanged. Our recent study in fibroblasts and macrophage-like RAW264.7 cells has revealed that the effect of KH176m on mPGES-1 expression is due to the inhibition of a PGE 2 -driven positive feedback controlloop of mPGES-1 transcriptional [35]. An effect of KH176m on PGE 2 production could, however, not be determined in the spheroid cultures because the amount of PGE 2 that was secreted during their growth was below the level of detection, despite the high level of mPGES-1 present in DU145 spheroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation